The relational Knowledge of Singular on Ernst Cassirer - Esparza, Gustavo (Pensamiento. Revista de Investigación e Información Filosófica, 2020)
This paper deepens the proposed solution on the knowledge of the singular developed by Ernst Cassirer. The problem arises that the relationship between the particular and the general is already conceived in the first studies of the author until crystallizing in his proposal to exchange substantive concepts for functional concepts. This methodological exchange will allow the neo-Kantian to base, eventually, (1) the Philosophie der Symbolischen Formen as a worldview that conceives culture as a universal criterion of meaning of all human actions and (2) the symbol as a harmonic functional unit between the singular and the universal.
Keywords: singular; universal; functionalism; symbolization; culture; Cassirer